Helicobacter pylori Is Associated With Precancerous and Cancerous Lesions of the Gastric Cardia Mucosa: Results of a Large Population-Based Study in China - Xie, Shuanghua; Wang, Shaoming; Xue, Liyan; Middleton, Daniel R. S.; Guan, Chentao; Hao, Changqing; Wang, Jinwu; Li, Bianyun; Chen, Ru; Li, Xinqing; Wei, Wenqiang (Frontiers in Oncology, 2020)
Background:Helicobacter pylori (H. pylori) is widely accepted to be the most important cause of gastric non-cardia adenocarcinoma (GNCA), while its role in the development of gastric cardia adenocarcinoma (GCA) is not well-defined. We aimed to investigate current H. pylori infection in relation to the severity of both precancerous and cancerous lesions of the gastric cardia in an Asian population at high risk of GCA. Methods: A population-based cross-sectional study was conducted in Linzhou County, Henan Province, China. Two thousand three (2,003) randomly selected participants with data on current H. pylori infection, assayed by 13C-urea breath test (13C-UBT), and a sequence of histological diagnoses of the gastric cardia mucosa were analyzed. Results: Of 2,003 subjects, 828 (41.33%) were currently infected with H. pylori. The prevalence of current H. pylori infection increased with increasing severity of histological lesions, from 34.12% in subjects with normal gastric cardia mucosa to 52.17% in subjects with gastric cardia high-grade intraepithelial neoplasia (CHIN)/ gastric cardia adenocarcinoma (GCA) (P for trend <0.001). With H. pylori-negative subjects as the reference category, H. pylori-positive subjects had statistically significant elevated adjusted prevalence odds ratios (PORs) for each of the histological lesions. The PORs (95% CI) were 2.15 (1.74–2.64), 3.46 (2.08–5.75), 2.78 (1.90–4.07), and 3.05 (1.30–7.17) for subjects with carditis, cardia intestinal metaplasia (CIM), cardia low-grade intraepithelial neoplasia (CLIN), and CHIN/GCA), respectively. The associations remained when subjects with abnormal stomach non-cardia mucosa were excluded. Conclusions: This large epidemiologic study demonstrates a positive association between current H. pylori infection and the severity of both precancerous and cancerous lesions of the gastric cardia in an Asian population at high risk of GCA. These findings suggest that H. pylori infection may play a role throughout both early- and late-stage development of GCA.